Metodologias ativas em ambientes virtuais de aprendizagem no curso de Turismo da UFPB à luz da aprendizagem significativa - Sousa, Magnun Bezerra de (2022)
This thesis seeks to explore the ways in which Significant Learning (SL) manifests itself in the use of active methodologies and Virtual Learning Environments (VLE), in the undergraduate program in tourism offered by the Federal University of Paraíba (UFPB), Brazil. Following a qualitative methodology of exploratory nature, the theoretical framework is anchored in the postulates formulated by American psychologist David Ausubel (1918-2008). At the same time, we conducted online, semi-structured interviews with faculty, and one focus group with students from the program in question. The information gathered was then analyzed, via content analysis, and it revealed that the principles of SL were not applied by professors exhaustively, neither were them identified in students’ perceptions of the learning processes of which they are part. Regarding the use of these active methodologies being facilitated by VLE, it was noticed that professors were more inclined toward developing interactionist teaching approaches, that is, in considering organic and environmental influencers in individuals’ formation. Finally, the data suggest that difficulties in teaching through VLE could be minimized if institutional training policies were more strongly applied.